Time to Recurrent Relapses Analysis in Schizophrenic Patients by Using Recurrent Events Model - Leila Cheraghi; Mehdi Rahgozar; Farbod Fadaei; Masuod Karimlou; Akbar Biglarian (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: Schizophrenia is to be emphasized due to its high prevalence, severity of symptoms and frequent recurrences. In this study the hazard of recurrence of Schizophrenia was analyzed by using recurrent events models. Materials & Methods: This study was an observational prospective study. Data was gathered from 159 registered schizophrenia patients at Razi Psychiatric Center. The type II conditional model and the frailty model were used for analyzing times of recurrence. SAS (version 9.1) and R (version 2.11.0) were used for analysis of data. Significance level for the statistical tests was considered to be 0.05. Results: In the type II conditional model, age at onset of disease (P=0.021) and marital status (P<0.001) only significantly affected the hazard of the first relapse. The effects of age at onset of disease, sex, marital status, how the disease began, history of head trauma and family history of schizophrenia were not significant on the hazard of the second relapse. History of head trauma had significant effect only on the hazard of the third relapse (P=0.020). In the frailty model only the effects of sex (P=0.014) and history of head trauma (P=0.014) were significant on the hazard of recurrent relapses. Conclusion: The effects of some covariates on the hazard of recurrent relapses were significant under type II conditional model, and some covariates had significant effect under the frailty model. Further research is needed to investigate the effect of other prognostic factors on the hazard of recurrent relapses and time of recurrent relapses.